2001
DOI: 10.1029/2000rs002395
|View full text |Cite
|
Sign up to set email alerts
|

Total solar eclipse effects on VLF signals: Observations and modeling

Abstract: Abstract.During the total solar eclipse observed in Europe on August 11, 1999, measurements were made of the amplitude and phase of four VLF transmitters in the frequency range 16-24 kHz. Five receiver sites wcrc set up, and significant variations in phase and amplitude are reported for 17 paths, more than any previously during an eclipse. Distances from transmitter to receiver ranged from 90 to 14,510 kin, although the majority were <2000 kin. Typically, positive amplitude changes were observed throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
1
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 19 publications
11
113
1
2
Order By: Relevance
“…The TRGCPs for five selected stations in the study vary between~400 and 7600 km (Table 1) and can be classified as short (<1000 km) and medium (1000-10,000 km) paths [Clilverd et al, 2001]. Clilverd et al [2001] for 11 August 1999 total SE observed both positive (increase) and negative (decrease) VLF amplitude changes (and in some cases both) which for majority of short paths were positive and negative for long paths. During 22 July 2009 total SE, Guha et al…”
Section: Experimental Setup and Datamentioning
confidence: 99%
See 4 more Smart Citations
“…The TRGCPs for five selected stations in the study vary between~400 and 7600 km (Table 1) and can be classified as short (<1000 km) and medium (1000-10,000 km) paths [Clilverd et al, 2001]. Clilverd et al [2001] for 11 August 1999 total SE observed both positive (increase) and negative (decrease) VLF amplitude changes (and in some cases both) which for majority of short paths were positive and negative for long paths. During 22 July 2009 total SE, Guha et al…”
Section: Experimental Setup and Datamentioning
confidence: 99%
“…discontinuty created by SE shadow [Clilverd et al, 2001] which depends mainly on the TRGCP length, path direction, topography of receiver sites, SE conditions, and ionospheric conditions along the TRGCP. The sudden increase in the D region reflection height due to SE causes some more significant modes reaching to receving stations and resulting in a complex interference pattern [Clilverd et al, 2001] of modes at the receiver sites.…”
Section: 1002/2013ja019521mentioning
confidence: 99%
See 3 more Smart Citations